Beyond The Classroom: Advantages of Indoor Plants - Kansas State University, K-State First (Kansas State University. K-State First., 2016)
A poster promoting the presentation "Advantages of Indoor Plants" at Kansas State University, hosted by Dr. Kim Williams, Professor of Greenhouse Management on October 24, 7-8 PM, in Derby Dining Center. Indoor plants contribute many benefits to the people around them. Learn what research from architects, engineers, NASA scientists, horticulturists, interior designers and psychologists shows about how plants influence human health, productivity, comfort and overall well-being.
Keywords: Beyond The Classroom; Events; Engagement; Community building; Application of learning; Horticulture; Posters